Asian American librarians and library services : activism, collaborations, and strategies - Clarke, Janet Hyunju, 1963-; Pun, Raymond, 1985-; Tong, Monnee, 1983-; Chu, Clara M., 1960- (Rowman & Littlefield, 2018)
"What are the library services and resources that Asian Pacific Americans need? What does it mean to be an Asian Pacific American librarian in the 21st century? In Asian American Librarians and Library Services: Activism, Collaborations, and Strategies, library professionals and scholars share reflections, best practices, and strategies, and convey the critical need for diversity in the LIS field, library programming, and resources to better reflect the rich and varied experiences and information needs of Asian Americans in the US and beyond. The contributors show that they care deeply about diversity, that they acknowledge that it is painfully lacking in so many aspects of libraries and librarianship, and that libraries and the LIS profession must systematically integrate diversity and inclusion into their strategic priorities and practices, indeed, in their very mission, such that the rich diversity of experiences and histories of Asian Americans in library and archival collections, services, and programming are not only validated and recognized, but also valued and celebrated as vital components of the shared American experience. The volume recognizes and honors the creative and intentional work librarians do for their constituent Asian American communities in promoting resources, services, and outreach."